Low-dose nesiritide in human anterior myocardial infarction suppresses aldosterone and preserves ventricular function and structure: a proof of concept study. Issue 16 (15th May 2009) - Chen, H H; Martin, F L; Gibbons, R J; Schirger, J A; Wright, R S; Schears, R M; Redfield, M M; Simari, R D; Lerman, A; Cataliotti, A; Burnett, J C
Abstract : Background: B-type natriuretic peptide (BNP, nesiritide) has anti-fibrotic, anti-hypertrophic, anti-inflammatory, vasodilating, lusitropic and aldosterone-inhibiting properties but conventional doses of BNP cause hypotension, limiting its use in heart failure. Objective: To determine whether infusion of low-dose BNP within 24 h of successful reperfusion for anterior acute myocardial infarction (AMI) would prevent adverse left ventricular (LV) remodelling and suppress aldosterone. Methods: A translational proof-of-concept study was carried out to determine tolerability and biological activity of intravenous BNP at 0.003 and 0.006 μg/kg/min, without bolus started within 24 h of successful reperfusion for anterior AMI. 24 patients with first anterior wall ST elevation AMI and successful revascularisation were randomly assigned to receive 0.003 (n = 12) or 0.006 (n = 12) μg/kg/min of IV BNP for 72 h in addition to standard care during hospitalisation for anterior AMI. Results: Baseline characteristics, drugs and peak cardiac biomarkers for myocardial damage were similar between both groups. Infusion of BNP at 0.006 μg/kg/min resulted in greater biological activity than infusion at 0.003 μg/kg/min as measured by higher mean (SEM) plasma cGMP levels (8.6 (1) vs 5.5 (1) pmol/ml, p<0.05) and suppression of plasma aldosterone (8.0 (2) to 4.6 (1) ng/dl, p<0.05), which was not seen in the 0.003 μg/kg/min group. LV ejection fraction (LVEF) improved significantly from baseline to 1 month (40 (4)% to 54 (5)%, p<0.05) in the 0.006 group but not in the 0.003 group. Infusion of BNP at 0.006 μg/kg/min was associated with a decrease of LV end-systolic volume index (61 (9) to 43 (8) ml/m 2, p<0.05) at 1 month, which was not seen in the 0.003 group. No drug-related serious adverse events occurred in either group. Conclusions: 72 h infusion of low BNP at the time of anterior AMI is well tolerated and biologically active. Patients treated with low-dose BNP had improved LVEF and smaller LV end-systolic volume at 1 month.